Intercultural Competence as a Premise for Professional and Personal Teacher Development: the Case of Master Degree Studies in Music Education - Lasauskienė, Jolanta; Wang, Xiangou; Zhang, Yiwei (Pedagogika, 2017)
The aim of the article is to analyse intercultural experience of foreign students enrolled in Master study programmes of Music Education, revealing tendencies in expression of intercultural competence and possibilities of its development in the university. The sample of the research included 27 foreign Master’s degree students (Chinese) of the Department of Music of the Faculty of Education at Lithuanian University of Educational Sciences. The research problem is determined by the question how intercultural competence of foreign Master students – future music educators – is expressed and what possibilities of its development at university are observed. Research methods. The data was collected in accordance with the method of written student reflections. The analysis of qualitative data was done through qualitative content analysis. The following conclusions are drawn in the article: Contemporary music educators have to be ready to conduct research, to critically evaluate and creatively improve current educational environment in terms of cultural, artistic and educational needs. Intercultural competence of music educators is determined as a person’s quality, an aggregate of knowledge, skills and attitudes that are necessary for successful activity of music educators in the context of interaction among different cultures. The results of the qualitative content analysis revealed that the foreign Master’s degree students in Lithuanian University of Educational Sciences relate music educator’s intercultural competence with knowledge and understanding of cultural phenomena, foreign language skills, involvement in musical cultural activities, ability to communicate with representatives of other cultures as well as with attitudes and personal qualities that facilitate music educator’s activities. Foreign students envisage a significant importance of intercultural knowledge, cultural identity and learning from other cultures to intercultural competence of music educators. Studies abroad are considered to be a priority factor in music educator’s intercultural competence, which encourages learning of other cultures, confirms importance of foreign language skills and opens a path towards personal and professional improvement. The results of the qualitative content analysis highlighted that the academic environment (study content and methods, relations between university teachers and students) has the most considerable impact on intercultural competence development.